Diferentes populações de uma Poaceae invasora respondem de maneira distinta ao aumento da salinidade. - Bora, Leticia Siman (2019)
Despite of the important role of macrophytes, some species can become invasive, overly growing and impairing the development of other organisms. In that mater, understanding environmental factors that can control growth of invader plants is of great importance. U. arrecta is a Poaceae with high invasive potential and one of the places where this macrophyte over develop is the Guaraguaçu river, the largest river of Paraná coastal plain. Along the river, this species distribution is uneven, and that could be caused by the saline gradient of the river. Salinity is one of the main factors that can determine macrophyte distribution along estuarine environments. We experimentally tested U. arrecta tolerance along a saline gradient, aiming to understand the reason of its uneven distribution along Guaraguaçu river. Furthermore, we also tested if the response to saline gradient depends on the population origin. We organized the experiment with three populations of this specie, hoping that populations near coastal environments were more resistant to high salinity. The experiment was carried out for forty days, and after that period we measured the development and growth of the macrophyte among four levels of salinity. Salinity was highly stressful for U. arrecta, and it was possible to observe a notorious difference among populations physiological responses, indicating evolutionary changes among populations. The impact of salinity on this macrophyte development was very clear in our experiment, however we concluded that salinity alone did not prevent its establishment, since almost all propagules developed roots in all saline treatments.